A construção do caso clínico, os impasses no laço do sujeito psicótico e a direção psicanalítica de tratamento em um dispositivo de saúde mental do SUS - Cardoso, Emilene Duarte Rocha (2022)
This research aims to understand which are the essential elements to the bu the psychoanalyticilding of a clinical case study of the psychotic subject, taking into account its unconscious desire and social bond begetting in the institutional context of psychosocial attention. To achieve this, we start by listening to teenagers with psychotic psychic structure in a clinical resource from the Unified Health System (SUS), — the Community Mental Health Centers (CAPS), equipment of mental health substitutes —, a deinstitutionalization proposal as well as epistemological deconstruction and critique regarding the medical and hospital-centered knowledge that is part of the psychiatric practice. This idea represents one of the facets of the production and conception of care capable of offering different transferential possibilities to the stalemates of bond subjectification. The Singular Therapeutic Project (PTS) presents itself as a care strategy, namely a set of therapeutic proposals that a multi-professional team debates over and conceives. We highlight that such questions were outlined from narratives observed in the clinic with psychotic subjects. These moments gave birth to some questions regarding the stalemates in clinical case study building and reflecting itself in the bond. Between these questions lie the clinical hearing implications of the subject in psychosis and where the analyst stands regarding psychoanalytic treatment. In other words, what is implicit in this institutional context to the listening to the subject's desire from the assumption of the clinical case study building. To do it so, an important point is the achieving of a connection between a clinic that supports itself through this listening and the SUS clinic. This can enable the keeping of a possible psychoanalytic clinic operator in psychosocial care